2010
DOI: 10.1073/pnas.1011233108
|View full text |Cite
|
Sign up to set email alerts
|

Differential dynamics and activity-dependent regulation of α- and β-neurexins at developing GABAergic synapses

Abstract: Neurexins (NRXs) and neuroligins are key synaptic adhesion molecules that also recruit synaptic signaling machineries. Neurexins consist of α-and β-isoforms, but how they couple synaptic transmission and adhesion to regulate activity-dependent synapse development remains unclear, in part because of poor understanding of their cell biology and regulation in the relevant neurons. Here, we examined the subaxonal localization, dynamics, and regulation of NRX1α and NRX1β in cortical perisomatic inhibitory synapses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…4G) and at extrasynaptic sites of the cell surface (Fig. 4H), consistent with the mobile behavior of its cognate receptor α-Nrxn on axonal membranes (36). Intracellularly, we observed gold-labeled Nxph1 over vesicular structures in the presynaptic terminal ( Fig.…”
Section: Expression Of Nxph1supporting
confidence: 58%
See 1 more Smart Citation
“…4G) and at extrasynaptic sites of the cell surface (Fig. 4H), consistent with the mobile behavior of its cognate receptor α-Nrxn on axonal membranes (36). Intracellularly, we observed gold-labeled Nxph1 over vesicular structures in the presynaptic terminal ( Fig.…”
Section: Expression Of Nxph1supporting
confidence: 58%
“…In addition, research has identified several molecules, mostly ion channels and receptors, which are functionally impaired when Nrxn expression is altered. Nrxn variants have been found to affect voltage-dependent calcium channels (9,10), GABA A R (7, 37), NMDAR (44), GABA B R (36,45), nicotinergic acetylcholine receptors (69), and AMPAR (47). These ionotropic and metabotropic receptors represent "target molecules" of Nrxn that may include some physical association, but it appears unlikely that the functional link to all these requires stable protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to identify potentiated synapses, our method uses antibodies specific for extracellular epitopes on GluR1 and neurexin-1β (Nrx1β) (Fig. 6D), a presynaptic adhesion molecule stabilized at the membrane surface by synaptic activity (43)…”
Section: Resultsmentioning
confidence: 99%
“…Thus, only a rigorous quantitative analysis with simultaneous presynaptic and postsynaptic labeling could reveal whether the cellular and subcellular specificity of synapse formation is compromised by transmission blockade in basket cell axons. This possibility warrants investigation because it would provide evidence that although synapse specificity might be guided by molecular cues, the execution of molecular cues in developing vertebrate circuits may be intertwined with and dependent on synaptic transmission, such as shown for the neurexin-neuroligin system (Fu and Huang, 2010).…”
Section: Role Of Transient Contacts and Their Activity-dependent Elimmentioning
confidence: 99%
“…In addition, we examined the effect of release blockade on the localization of the essential synaptic adhesion molecule neurexin1␤. We recently developed a method to detect the membrane-inserted form of neurexin1 and showed that neurexin1␤ is specifically localized to presynaptic boutons of basket interneurons (Fu and Huang, 2010). In control cells, Nrx1␤-SEP (a neurexin1␤-synaptopHlorin fusion protein) was often concentrated to a restricted area within a bouton with variable sizes among different boutons (Fig.…”
Section: Gaba Transmission Is Not Necessary For Inhibitory Synapse Fomentioning
confidence: 99%